Influence of body fat on heart rate variability in healthy females - Hiba Salih Mahdi Al-Khassaki; Bassam Talib Al-Galani (Journal of the Pakistan Medical Association)
Objective: To evaluate the effect of central obesity indices in healthy females on cardiac autonomic activity, using heart rate variability as an index reflecting the cardiac autonomic balance. Method: The cross-sectional study was conducted at the Department of Physiology, College of Medicine, Mustansiriyah University, Baghdad, Iraq, from September 2020 to April 2021, and comprised adult healthy women having a regular menstrual cycle who were not consumers of tobacco, alcohol or any medication. Waist circumference, waist-hip ratio, waist-height ratio and lipid accumulation product measurements were noted for each subject. Repeated blood pressure and heart rate measurements were taken on the brachial artery of the right arm until stable values were achieved. Heart rate variability was based on electrocardiogram data related to R-R interval. Data was analysed using GraphPad InStat version 3.06. Results: There were 53 women with mean age 37.4±10.5 years. Low-frequency power normalised units at the highest two quintiles of waist circumference was significantly higher than the lowest two quintiles (p<0.03), and significantly and positively correlated with waist-hip ratio (p<0.02) and waist-height ratio (p<0.05). At the highest two quintiles of lipid accumulation product, low-frequency power normalised units value was significantly higher than at the lowest two quintiles (p<0.02). Conclusion: Increased waist circumference, waist-height ratio, waist-hip ratio and lipid accumulation product values were significantly associated with high sympathetic tone. Key Words: Abdominal, Circumference, Hip Ratio, Blood Pressure, Arm, Brachial Artery, Heart Rate, Lipid Accumulation, Electrocardiography, Menstrual Cycle